2015
DOI: 10.1111/age.12281
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of body growth and immunity-related differentially expressed genes through deep RNA sequencing in the piglets of Jeju native pig and Berkshire

Abstract: This study was carried out with the objective to investigate the differentially expressed genes (DEGs) between Jeju native pig (JNP) and Berkshire piglets. The RNA-Seq technique was used to investigate the transcriptomes in the fat, liver and longissimus dorsi muscle from these two breeds. Paired-end reads of the sequences that passed the quality filters were aligned to the Sus scrofa genome using tophat2 (v2.0.2). In this study, 65% of muscle, 20% of fat and 54% of liver genes showed higher expression in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Next-generation sequencing (NGS) is a term that includes several high-throughput sequencing technologies including but not limited to: Illumina, Roche 454 and SOLiD sequencing and RNA-Seq (van Dijk et al, 2014). RNA-Seq for example, has been used to investigate differentially expressed genes in the transcriptome of different breeds of pig (Ghosh et al, 2015), which showed that genes involved in body growth and the immune system were more highly expressed in Berkshire pigs compared to Jeju native pigs. RNA-seq has also been used to identify genes and inhibitory, non-coding microRNA (miRNAs) that are differentially expressed between pigs with different feed efficiencies (Jing et al, 2015;Brameld and Parr, 2016).…”
Section: Next Generation Sequencingmentioning
confidence: 99%
“…Next-generation sequencing (NGS) is a term that includes several high-throughput sequencing technologies including but not limited to: Illumina, Roche 454 and SOLiD sequencing and RNA-Seq (van Dijk et al, 2014). RNA-Seq for example, has been used to investigate differentially expressed genes in the transcriptome of different breeds of pig (Ghosh et al, 2015), which showed that genes involved in body growth and the immune system were more highly expressed in Berkshire pigs compared to Jeju native pigs. RNA-seq has also been used to identify genes and inhibitory, non-coding microRNA (miRNAs) that are differentially expressed between pigs with different feed efficiencies (Jing et al, 2015;Brameld and Parr, 2016).…”
Section: Next Generation Sequencingmentioning
confidence: 99%
“…RNA-seq using NGS technology has become widely used for high-throughput researches of gene expression. Such technology has been successfully used to identify genes associated with economically important quantitative traits, such as body growth, immune, disease resistance, and meat quality (Mu et al, 2014; Sodhi et al, 2014; Ghosh et al, 2015; Xiao et al, 2015). In this study, we compared the gene expression difference in the whole blood samples of DPL and Landrace pigs 6 h after stimulation with class C CpG ODN 2429 (a TLR9 agonist) in vivo using RNA-seq technology.…”
Section: Introductionmentioning
confidence: 99%
“…The JNP has black skin, erect, unfolded ears and is well-known for its tender and juicy meat. Consumers prefer JNP meat because of its superior taste, tenderness and marbling quality compared to the meat from western breeds [2]. JNP meat can be regarded as one of the best pork in Korea.…”
Section: Introductionmentioning
confidence: 99%